The Social Foundations of the Bureaucratic Order - Kallinikos, Jannis (Organization (London, England), 2004)
This article views the bureaucratic form of organization as both an agent and an expression of key modern social innovations that are most clearly manifested in the non-inclusive terms by which individuals are involved in organizations. Modern human involvement in organizations epitomizes and institutionally embeds the crucial yet often overlooked cultural orientation of modernity whereby humans undertake action along well-specified and delimited paths thanks to their capacity to isolate and suspend other personal or social considerations. The organizational involvement of humans qua role agents rather than qua persons helps unleash formal organizing from being tied to the indolence of the human body and the languish process of personal or psychological reorientation. Thanks to the loosening of these ties, the bureaucratic organization is rendered able to address the shifting contingencies underlying modern life by reshuffling and re-assembling the roles and role patterns by which it is made. The historically unique adaptive capacity of bureaucracy remains, though hidden behind the ubiquitous presence of routines and standard operating procedures that are mistakenly exchanged for the essence of the bureaucratic form.